Improvement in White Matter Tract Reconstruction with Constrained Spherical Deconvolution and Track Density Mapping in Low Angular Resolution Data: A Pediatric Study and Literature Review - Toselli, Benedetta; Tortora, Domenico; Severino, Mariasavina; Arnulfo, Gabriele; Canessa, Andrea; Morana, Giovanni; Rossi, Andrea; Fato, Marco Massimo (Frontiers in Pediatrics, 2017)
Introduction: Diffusion-weighted magnetic resonance imaging (DW-MRI) allows noninvasive investigation of brain structure in vivo. Diffusion tensor imaging (DTI) is a frequently used application of DW-MRI that assumes a single main diffusion direction per voxel, and is therefore not well suited for reconstructing crossing fiber tracts. Among the solutions developed to overcome this problem, constrained spherical deconvolution with probabilistic tractography (CSD-PT) has provided superior quality results in clinical settings on adult subjects; however, it requires particular acquisition parameters and long sequences, which may limit clinical usage in the pediatric age group. The aim of this work was to compare the results of DTI with those of track-density maps (TDI) and CSD-PT on data from neonates and children, acquired with low angular resolution and low b-value diffusion sequences commonly used in pediatric clinical MRI examinations. Materials and methods: We analyzed DW-MRI studies of 50 children (8 neonates aged 3 to 28 days, 20 infants aged 1 to 8 months, and 22 children aged 2 to 17 years) acquired on a 1.5T Philips scanner using 34 gradient directions and a b-value of 1000 s/mm2 . Other sequence parameters included 60 axial slices; acquisition matrix, 128×128; average scan time 5:34 minutes; voxel size 1.75×1.75×2 mm; one b=0 image. For each subject, we computed principal eigenvector (EV) maps and directionally-encoded color TDI maps (DEC-TDI) from whole-brain tractograms obtained with CSD-PT; the cerebellar-thalamic, cortico-pontocerebellar, and corticospinal tracts were reconstructed using both CSD-PT and DTI. Results were compared by two neuroradiologists using a five-point qualitative score. Results: The DEC-TDI maps obtained presented higher anatomical detail than EV maps, as assessed by visual inspection. In all subjects, WM tracts were successfully reconstructed using both tractography methodologies. The mean qualitative scores of all tracts obtained with CSD-PT were significantly higher than those obtained with DTI (p-value < 0.05 for all comparisons). Conclusions: CSD-PT can be successfully applied to DW-MRI studies acquired at 1.5T with acquisition parameters adapted for pediatric subjects, thus providing TDI maps with great anatomical detail. This methodology yields satisfactory results for clinical purposes in the pediatric age group.